National Security vs. Political Image: Framing of Operation Zarb-e-Azb in Pakistani Dailies - Rubab Musarrat, (Journal of Peace, Development and Communication, 2021)
National security Vs. Political image in Pakistan are always in search of common ground. Historically, military forces and civilian leadership in Pakistan struggle to find the right balance and the civilian leadership has hardly commanded the gun. Frame building has been described as the flow of frames from national security image to political actors to editors and, thus, to editorials. To find out to what extent the national security image influence more as compared to national political image, this research identified the issue-specific frames of the military operation Zarb-e-Azb, measured their presence in editorials of three Pakistani English newspapers, Dawn, The Nation, and The News from June 2014 to June 2016. The quantitative content analysis is used to investigate the role of print media in covering OZA. The results of the study revealed that the slant, style, themes used in the editorials of the selected newspapers almost remained the same, appreciating the military institutions positively. Whereas condemning the civilian leadership for their lack of concern towards implementing the already approved Nation Action Plan. The study revealed that the media supported the national security image more as compared to political image in view of Operation Zarb-e-Azb (OZA) in the war against terrorism. The civil military relationship was negatively framed by Pakistani press under the context of Zarb-e-Azb Operation.